Indicators of problems evaluated by parents and children stratified by birth weight - Rodrigues-palucci, Claudia Mazzer [UNESP]; Loureiro, Sonia Regina (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2017)
Studies on the impact of birth weight on child development require the participation of children as informants. The objective of this study was to compare the indicators of behavioral problems and depression in a cohort of school-age children stratified by birth weight and to investigate possible associations between the indicators of behavioral problems, evaluated by the parents, and depression, evaluated by the children. A total of 665 children, aged 10-11 years, distributed into five birth-weight groups were evaluated. The parents responded to the Strengths and Difficulties Questionnaire, and the children responded to the Children's Depression Inventory. It was found that there were: (a) significantly more indicators of hyperactivity and depression in the children born with very low birth weight; (b) associations between the indicators of childhood depression and the indicators of overall behavioral problems in all weight groups evaluated, except for the very low birth weight group. There was good consistency between the ratings of problems by children and parents.

Estudos sobre o impacto do peso ao nascer para o desenvolvimento infantil carecem da inclusão das crianças como informantes. Objetivou-se comparar os indicadores de problemas comportamentais e de depressão apresentados por crianças, em idade escolar, de uma coorte estratificada pelo peso ao nascer, e verificar as possíveis associações entre os indicadores comportamentais, avaliados pelos pais, e de depressão, informados pelas crianças. Foram avaliadas 665 crianças, aos 10-11 anos de idade, distribuídas em cinco grupos de peso ao nascer. Os pais responderam ao Questionário de Capacidades e Dificuldades, e as crianças responderam ao Inventário de Depressão Infantil. Constatou--se: (a) significativamente mais indicadores de hiperatividade e de depressão nas crianças nascidas com muito baixo peso; (b) associações entre os indicadores de depressão infantil e os problemas comportamentais gerais para todos os grupos de peso, com exceção do muito baixo peso. Verificou-se consistência na avaliação de problemas por parte das crianças e pais.
Indicadores de problemas avaliados por pais e crianças estratificadas pelo peso ao nascer
Keywords: Behavior; Birth weight; Depression; Parent-child relations; Comportamento; Peso ao nascer; Depressão; Relações pais-filho